2016
DOI: 10.4274/jus.2015.613
|View full text |Cite
|
Sign up to set email alerts
|

To Save or not to Save the Kidney: Relieving Unilateral Obstruction May Significantly Improve an Initially Low Split Renal Creatinine Clearance

Abstract: What's known on the subject? and What does the study add? ÖZ AmaçÇalışmamızda akut/subakut tek taraflı komplet üreteral tıkanıklığa bağlı böbrek fonksiyonlarının nefrostomi ile tedavi sonrası değişimini göstermek amaçlanmıştır. gereç ve yöntemOtuz hasta prostpektif olarak çalışmaya dahil edilmiştir. Hepsinin üreter taşı olup 24'ünde (%80) üst üreter ve 6'sında (%20) orta üreter yerleşimliydi. Tüm hastaların ileri düzeyde hidronefrozu olduğu için perkütan nefrostomi takılması planlandı. Nefrostomi takıldıktan s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In another study, after a moderate renal I/R, A779 alone or A779 + PD123319 (AT2R antagonist) infusion increased the RBF and RVR responses to Ang II infusion significantly in females but not in the male rats [101], so that simultaneous AT2R and MasR blockade decreased renal vasoconstriction following Ang II infusion. Unilateral ureteral obstruction (UUO) via producing local vasoactive factors leads to increased RVR, decreased RBF, and renal hemodynamic impairment [102, 103]. Hassanshahi and Nematbakhsh showed that Ang 1-7 infusions significantly increased RBF and decreased RVR in sham, UUO, and RUUO (UUO removal) groups [104].…”
Section: Mas Receptormentioning
confidence: 99%
“…In another study, after a moderate renal I/R, A779 alone or A779 + PD123319 (AT2R antagonist) infusion increased the RBF and RVR responses to Ang II infusion significantly in females but not in the male rats [101], so that simultaneous AT2R and MasR blockade decreased renal vasoconstriction following Ang II infusion. Unilateral ureteral obstruction (UUO) via producing local vasoactive factors leads to increased RVR, decreased RBF, and renal hemodynamic impairment [102, 103]. Hassanshahi and Nematbakhsh showed that Ang 1-7 infusions significantly increased RBF and decreased RVR in sham, UUO, and RUUO (UUO removal) groups [104].…”
Section: Mas Receptormentioning
confidence: 99%
“…A better understanding of its pathogenesis and deploying effective therapies may reduce the global burden of end-stage renal disease. The therapeutic strategies of UUO have remained as main goal for urologists and nephrologists [3].…”
Section: Introductionmentioning
confidence: 99%